The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1002/uog.17445
|View full text |Cite
|
Sign up to set email alerts
|

Non‐visualization of choroid plexus of fourth ventricle as first‐trimester predictor of posterior fossa anomalies and chromosomal defects

Abstract: Non-visualization of the CP-4V in the first trimester appears to be a strong marker of posterior fossa anomalies and chromosomal defects. Qualitative evaluation of this anatomic structure is simple, feasible and reproducible, and its routine assessment during the first-trimester scan may facilitate the early detection of CNS anomalies and associated fetal aneuploidy. Copyright © 2017 ISUOG. Published by John Wiley & Sons Ltd.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
40
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(44 citation statements)
references
References 29 publications
2
40
2
Order By: Relevance
“…Volpe et al [13] expressed that the pregnancy was terminated in 71% (12/17) of the cases who had abnormal image in the posterior fossa. In the study of Martinez-Ten et al, [23] the rate of ended or terminated case was 82% (23/28) after similar findings. In our series, the rate of ended-terminated cases we found after actual negatives were determined was 84% (21/25), and it was similar to other studies.…”
Section: Discussionmentioning
confidence: 56%
See 3 more Smart Citations
“…Volpe et al [13] expressed that the pregnancy was terminated in 71% (12/17) of the cases who had abnormal image in the posterior fossa. In the study of Martinez-Ten et al, [23] the rate of ended or terminated case was 82% (23/28) after similar findings. In our series, the rate of ended-terminated cases we found after actual negatives were determined was 84% (21/25), and it was similar to other studies.…”
Section: Discussionmentioning
confidence: 56%
“…When we interpreted our findings together with further examinations, we determined that this was caused by chromosomal anomalies in particular. Martinez-Ten et al [23] reported in their study that there was an increase in NT in 50% of IT(-) cases and 71% of the entire group had major chromosomal anomalies. When we excluded false negative cases, the rate of major chromosomal anomaly was 48%.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…Later studies found that there may be some fluid in the region of the IT, but the volume is reduced 9,23 . Furthermore, in OSB fetuses, the cisterna magna is typically not identifiable and the CP of the fourth ventricle is abnormal, being not visible or stuck to the occipital bone 25,26 . In our clinical experience, we have found that the most powerful ultrasound marker of OSB in early gestation is a BS/BSOB ratio > 1 6,9 . In the current study, among the 30 cases with appropriate images available in the midsagittal view, all had a BS/BSOB ratio > 1 and 19 had reduced IT.…”
Section: Discussionmentioning
confidence: 99%